Measurement of the t t ¯ $$ t\overline{t} $$ production cross-section in pp collisions at s $$ \sqrt{s} $$ = 5.02 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; B. Abbott; D. C. Abbott; K. Abeling; S. H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A. C. Abusleme Hoffman; B. S. Acharya; et al. (Journal of High Energy Physics, 2023)
Abstract The inclusive top-quark pair ( t t ¯ $$ t\overline{t} $$ ) production cross-section σ t t ¯ $$ σ_{t\overline{t}} $$ is measured in proton–proton collisions at a centre-of-mass energy s $$ \sqrt{s} $$ = 5.02 TeV, using 257 pb −1 of data collected in 2017 by the ATLAS experiment at the LHC. The t t ¯ $$ t\overline{t} $$ cross-section is measured in both the dilepton and single-lepton final states of the t t ¯ $$ t\overline{t} $$ system and then combined. The combination of the two measurements yields σ t t ¯ = 67.5 ± 0.9 stat . ± 2.3 syst . ± 1.1 lumi . ± 0.2 beam pb , $$ σ_{t\overline{t}}=67.5± 0.9\left(stat.\right)± 2.3\left(syst.\right)± 1.1\left(lumi.\right)± 0.2\left(beam\right)pb, $$ where the four uncertainties reflect the limited size of the data sample, experimental and theoretical systematic effects, and imperfect knowledge of both the integrated luminosity and the LHC beam energy, giving a total uncertainty of 3.9%. The result is in agreement with theoretical quantum chromodynamic calculations at next-to-next-to-leading order in the strong coupling constant, including the resummation of next-to-next-to-leading logarithmic soft-gluon terms, and constrains the parton distribution functions of the proton at large Bjorken-x.